2013
DOI: 10.1093/infdis/jit806
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Associated With Acute Respiratory Infections and Influenza-like Illness Among Outpatients From the Influenza Incidence Surveillance Project, 2010–2011

Abstract: Background The Influenza Incidence Surveillance Project (IISP) monitored outpatient acute respiratory infection (ARI; defined as the presence of ≥2 respiratory symptoms not meeting ILI criteria) and influenza-like illness (ILI) to determine the incidence and contribution of associated viral etiologies. Methods From August 2010 through July 2011, 57 outpatient healthcare providers in 12 US sites reported weekly the number of visits for ILI and ARI and collected respiratory specimens on a subset for viral test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 32 publications
12
84
0
1
Order By: Relevance
“…25 In a large study in outpatients with ILI from the United States, HRVs/HEVs were the most commonly detected viruses (after influenza), with an overall detection rate of 21%. 26 The findings of these different studies are in broad agreement with those presented herein.…”
Section: Discussionsupporting
confidence: 89%
“…25 In a large study in outpatients with ILI from the United States, HRVs/HEVs were the most commonly detected viruses (after influenza), with an overall detection rate of 21%. 26 The findings of these different studies are in broad agreement with those presented herein.…”
Section: Discussionsupporting
confidence: 89%
“…This difference may be due to the non-temperate climate in our region, as higher activity of influenza virus can be encountered in regions with a humid climate [21]. On the other hand, our rhinovirus detection rates were very close to those of influenza virus, and our results agreed with a large IISP of outpatients from the United States in that the predominant virus was influenza, closely followed by rhinovirus, among adult patients 18-64 years of age [2].…”
Section: Discussionsupporting
confidence: 82%
“…Although bacterial etiology might sometimes be encountered, the majority of ILI cases are caused by viral pathogens [1]. Epidemic peaks during the winter months are usually caused by influenza virus and respiratory syncytial virus (RSV), while other viruses such as human metapneumovirus (MPV) and parainfluenza viruses (PIVs) also circulate in fall and winter [2]. There is a corresponding winter increase in presentations to emergency departments and outpatient clinics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of ILI was similar to that in other settings-in the United States, the national baseline among outpatients is 2.0%, with increases up to 4.6% during seasonal peaks. 12,13 There are few published data regarding patterns of influenza in Sri Lanka, but surveillance samples tested by the national reference laboratory, Medical Research Institute (MRI), showed that the prevalence of laboratory-confirmed influenza among outpatients presenting with ILI to sentinel hospital sites was 12% in 2011 and 16% in 2012. 14 The proportion of influenza in this study was much higher than documented in prior years and was initially largely under recognized, which highlights the need for continued surveillance and testing from all regions of the country.…”
Section: Discussionmentioning
confidence: 99%